Trajectories of Instrumental and Emotional Social Support and the Associated Risk of Mortality in Bereaved Older Adults in Taiwan. (July 2023) - Tzeng, Huei-Jia; Lee, Chiachi Bonnie; Chen, Cheng-Tsung; Lee, Miaw-Chwen
This study identified the trajectories of instrumental and emotional perceived social support (PSS) from 1996 to 2003 and investigated the associated risk of mortality in bereaved older adults in Taiwan. The study analyzed 1, 188 bereaved older adults who had experienced loss of a spouse, a child, or both before 1996 from the Taiwan Longitudinal Study on Aging. More favorable trajectories of PSS are associated with lower mortality risk in bereaved older adults. Compared with the spousal or dual bereavement, the parental bereavement benefited more from consistently high instrumental PSS. The present study revealed that consistently high emotional PSS had a stronger protective effect on mortality risk for a widow or widower than did consistently high instrumental support. The findings of this study can serve as an empirical reference to inform social policies and clinical practices for bereaved older adults in culturally similar societies.